Percepción de calidad de vida de los cuidadores de pacientes con enfermedad de Huntington (2023)
Family caregivers do not have the psychosocial tools to offer comprehensive care to their family members with Huntington's disease (EH); a disabling condition with a great impact on the quality of life of those who suffer from it and those who care for them. The objective of the research was to explore the perception built by the caregivers of patients with EH in some municipalities of the Colombian Caribbean coast, on the quality of life, from the physical, psychological and social dimensions. A qualitative methodology with a narrative biographical approach was used, semistructured interviews were conducted with 10 caregivers, under the parameters of the Schwartzmann Health-Related Quality of Life (HRQL) model, which assumes quality of life from a multidimensional and continuous position. Movement, with interaction of internal and external factors that seek to offer conceptual elements for a greater understanding of the psychosocial determinants of health-related quality of life. In the results, 3 categories were identified that show the conditions of poverty in which they live, the unsatisfied basic needs, the particularity, and the way in which they feel and perceive their reality, among the points of convergence of the caregivers, generated by the rarity of the EH., there is the search for knowledge to provide adequate care. The caregivers presented deterioration in the quality of life related to health: they experienced changes at the biopsychosocial level and neglect of themselves, suffering physical, psychological and social alterations, they made known all the emerging feelings in these caregivers such as deep sadness and uncertainty, from where faith springs as a coping mechanism, denoting resilience and hope in these informal family caregivers. This study allowed to know from what they feel, express and do in their sociocultural context, the serious social, physical, psychological and economic problems that caregivers experience.